Trauma induced heterotopic ossification patient serum alters mitogen activated protein kinase signaling in adipose stem cells. Issue 9 (10th April 2018) - Martin, Elizabeth C.; Qureshi, Ammar T.; Llamas, Claire B.; Boos, Elaine C.; King, Andrew G.; Krause, Peter C.; Lee, Olivia C.; Dasa, Vinod; Freitas, Michael A.; Forsberg, Jonathan A.; Elster, Eric A.; Davis, Thomas A.; et al.
Abstract : Post‐traumatic heterotopic ossification (HO) is the formation of ectopic bone in non‐osseous structures following injury. The precise mechanism for bone development following trauma is unknown; however, early onset of HO may involve the production of pro‐osteogenic serum factors. Here we evaluated serum from a cohort of civilian and military patients post trauma to determine early induction gene signatures in orthopaedic trauma induced HO. To test this, human adipose derived stromal/stem cells (hASCs) were stimulated with human serum from patients who developed HO following trauma and evaluated for a gene panel with qPCR. Pathway gene analysis ontology revealed that hASCs stimulated with serum from patients who developed HO had altered gene expression in the activator protein 1 (AP1) and AP1 transcriptional targets pathways. Notably, there was a significant repression in FOS gene expression in hASCs treated with serum from individuals with HO. Furthermore, the mitogen‐activated protein kinase (MAPK) signaling pathway was activated in hASCs following serum exposure from individuals with HO. Serum from both military and civilian patients with trauma induced HO had elevated downstream genes associated with the MAPK pathways. Stimulation of hASCs with known regulators of osteogenesis (BMP2, IL6, Forskolin, and WNT3A) failed to recapitulate the gene signature observed in hASCs following serum stimulation, suggesting non‐canonical mechanisms for gene regulation in trauma induced HO. These findings provide new insight for the development of HO and support ongoing work linking the systemic response to injury with wound specific outcomes. Abstract : Post‐traumatic heterotopic ossification (HO) is the formation of ectopic bone in non‐osseous structures following injury. This study uses patient serum from high blast trauma to identify novel mechanism for HO formation. We have identified the AP1 transcription factor network as a possible mechanism for ectopic bone formation in individuals with HO.